Recovery of impaired microvascular function in collateral dependent myocardium after recanalisation of a chronic total coronary occlusion. Issue 11 (14th October 2004) - Werner, G S; Emig, U; Bahrmann, P; Ferrari, M; Figulla, H R
Abstract : Objective: To assess the potential for recovery of impaired microvascular function in collateral dependent myocardium after recanalisation of a chronic total coronary occlusion and the determinants of this recovery. Patients and design: 120 patients underwent a successful recanalisation of a chronic total coronary occlusion (duration > 2 weeks) and a follow up angiography after a mean (SD) of 5.0 (1.2) months. The coronary flow velocity reserve (CFVR) and the fractional flow reserve were measured after recanalisation and at follow up. Global and regional left ventricular (LV) function were analysed by quantitative angiography. Results: Microvascular dysfunction, defined by a CFVR < 2.0 and a fractional flow reserve ⩾ 0.75, was observed in 55 (46%) patients after recanalisation. Microvascular function improved during follow up in 24 (20%). The CFVR increased during follow up from 2.01 (0.58) to 2.50 (0.79) (p < 0.001), due to a decrease in basal average peak velocity from 30.7 (14.9) cm/s to 25.5 (13.3) cm/s (p = 0.001). Improved microvascular function was associated with an improved regional LV function, shown by a correlation between increased wall motion severity index and increased CFVR ( r = 0.38, p = 0.003). The major determinant of microvascular dysfunction at baseline was the presence of diabetes mellitus (odds ratio 4.3, 95% confidence interval 1.8 to 10.2), which remained so at follow up (odds ratio 4.1, 95% confidence interval 1.3 to 13.4). Improvement of LV function was not impaired by the presence of microvascular dysfunction after recanalisation. Conclusions: The frequently observed microvascular dysfunction after recanalisation of a chronic total coronary occlusion is a transient phenomenon in most patients and is influenced by the presence of diabetes mellitus. It does not impede the recovery of LV function. Improved regional LV function is associated with improved microvascular function.